Pengaruh Shopping Lifestyle, Fashion Involvement Dan Discount Product Terhadap Impulse Buying Behavior Pada Konsumen Thrift Shop Kota Malang - Pranata, Steven Arya; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The aim of research using this type of explanatory research and quantitative approach is to determine and analyze the influence of shopping lifestyle, fashion involvement and discount products on the impulse buying behavior of students in Malang City, both simultaneously and partially. The population of this research is students in the city of Malang who make purchases at thrift shops whose number is unknown. The sampling technique used was the Malhotra formula, determining the number of uncounted samples or populations of at least 5 x the number of indicators used in the research which was then found to be 85 respondents. This research method uses multiple linear regression analysis with SPSS analysis tools. Based on the results of this research, shopping lifestyle, fashion involvement and discount products simultaneously have a significant influence on the impulse buying behavior of students in Malang City. Partially, shopping lifestyle, fashion involvement and discount products all have a positive and significant influence on the impulse buying behavior of students in Malang City. Keywords: Shopping Lifestyle, Fashion Involvement, Discount Product And Impulse Buying Behavior